2017
DOI: 10.1038/s41559-017-0395-0
|View full text |Cite
|
Sign up to set email alerts
|

Local loss and spatial homogenization of plant diversity reduce ecosystem multifunctionality

Abstract: Biodiversity is declining in many local communities while also becoming increasingly homogenized across space. Experiments show that local plant species loss reduces ecosystem functioning and services, but the role of spatial homogenization of community composition and the potential interaction between diversity at different scales in maintaining ecosystem functioning remains unclear, especially when many functions are considered (ecosystem multifunctionality). We present an analysis of eight ecosystem functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
192
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 212 publications
(219 citation statements)
references
References 38 publications
8
192
1
2
Order By: Relevance
“…This requires understanding the role of biodiversity across the range of diversity present in nature, relative to environmental conditions, when evaluating how biodiversity structures functions. While not their main focus, both van der Plas et al (2016) and Hautier et al (2018) found that, across large spatial extents (forests across Europe and grasslands across the world), environmental variation had a comparable to sometimes greater effect on multifunctionality than biodiversity. It is conceivable that at large spatial scales, environmental conditions among sites could either overwhelm or enhance any effect of diversity on ecosystem function.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This requires understanding the role of biodiversity across the range of diversity present in nature, relative to environmental conditions, when evaluating how biodiversity structures functions. While not their main focus, both van der Plas et al (2016) and Hautier et al (2018) found that, across large spatial extents (forests across Europe and grasslands across the world), environmental variation had a comparable to sometimes greater effect on multifunctionality than biodiversity. It is conceivable that at large spatial scales, environmental conditions among sites could either overwhelm or enhance any effect of diversity on ecosystem function.…”
Section: Introductionmentioning
confidence: 99%
“…Widespread evidence exists for a positive relationship between diversity, typically measured as plant species richness, and ecosystem functioning, most often measured as plant productivity. However, the nature of biodiversity-ecosystem function relationships in real-world systems, characterized by high environmental heterogeneity that shapes patterns of biodiversity, remains unresolved (van der Plas et al 2016, Duffy et al 2017, Hautier et al 2018. However, the nature of biodiversity-ecosystem function relationships in real-world systems, characterized by high environmental heterogeneity that shapes patterns of biodiversity, remains unresolved (van der Plas et al 2016, Duffy et al 2017, Hautier et al 2018.…”
Section: Introductionmentioning
confidence: 99%
“…What are the main drivers for spatial beta diversity and are those drivers the same over the decades? Studying these issues is important, as it has been found that spatial homogenisation of plant diversity reduces ecosystem multifunctionality (Hautier et al 2018). different beta diversity facets).…”
Section: Introductionmentioning
confidence: 99%
“…Because of the many ecosystem services that they provide, grasslands are increasingly the focus of conservation and ecological restoration (Hautier et al 2018). Efforts range from establishing grassland vegetation on road verges to restoring prairie communities and ecosystem functions to establishing multifunctional grasslands: seminatural communities that produce multiple ecosystem services including agricultural commodities (Jordan and Warner 2010, Auestad et al 2015, Harmon-Threatt and Hendrix 2015.…”
Section: Introductionmentioning
confidence: 99%
“…These include the failure of translocated populations to establish or persist (Vander Mijnsbrugge et al 2010) and excessive dominance of the restored or seminatural (hereafter "restored") community by translocated populations (Baer et al 2005). Excessive dominance by one species can alter community assembly (Polley et al 2005) and reduce the community diversity and resilience (Peterson et al 1998, Baer et al 2005) that contribute to ecosystem stability, function, and services (Cadotte et al 2012, Hautier et al 2018. Excessive dominance by one species can alter community assembly (Polley et al 2005) and reduce the community diversity and resilience (Peterson et al 1998, Baer et al 2005) that contribute to ecosystem stability, function, and services (Cadotte et al 2012, Hautier et al 2018.…”
Section: Introductionmentioning
confidence: 99%